À REAL BIBLIOTHECA PUBLICA DE LISBOA PELO SEU INSPIRADO ESTABELECIMENTO EM UTILIDADE E CREDITO NACIONAL DOS SEUS LIVROS: O UNIVERSO DO CONHECIMENTO E DOS LIVROS NAS CARTAS DO FREI MANUEL DO CENÁCULO - Pillati, Jamaira Jurich (2015)
This research aimed to analyze the representations of books, libraries and literate in Portugal in the eighteenth century, considering the political and cultural issues raised by Enlightenment ideas as regards the epoch. For this, the speeches produced by two Portuguese literates recognized, Manuel do Cenáculo Villas Boas Annes and António Ribeiro dos Santos were explored. Manuel do Cenáculo, the well known Bishop of Beja, was illustrated active in Pombal reform with regard to the teaching and books policies, working with the Royal Literary Censorship Board and the Literaly Board of reform at the University of Coimbra. António Ribeiro dos Santos took over the organization of the University Library at this same time and later, during the reign of D. Maria I, took over as chief librarian of the Royal National Library. From 1796 to 1798, the Cenáculo and Ribeiro kept private correspondence regarding a donation from first to the Royal National Library, under the administration of the second. The research was conducted with the correspondence established between them, as well as the catalog of the works donated to the Library. Seeking input on the concept of Chartier representations in discourse analysis methodology, in the History of Culture Writing and Reading and theoretical review about the complexity of the Enlightenment understanding of the Portuguese Empire, the research deepened on what meant the books and libraries to the ideal of State credited to literate then, of which we hope to prove, Cenáculo and Ribeiro dos Santos, are good examples.